Agricultural diversification as an adaptation strategy - López Noriega, Isabel; Dawson, Ian K.; Vernooy, Ronnie; Köhler-Rollefson, Ilse; Halewood, Michael (2017)
The role of agricultural biodiversity for sustaining ecosystem services crucial for food and agriculture becomes particularly relevant in the face of climate change, and has been widely recognised as a central part of climate-smart agriculture (CSA) since the concept was first launched in 2010. The utilisation of agricultural biodiversity in risk reduction and climate adaptation strategies has continued to attract attention, particularly as a component of micro-level strategies oriented towards diversification of production on farm, and land management measures aiming to improve resilience at landscape scale. Despite ample evidence of the value of agricultural biodiversity (including genetic resources) in climate change adaptation, the scalability of biodiversity-based measures is limited as they are often context specific and may have a lower relative value when compared to other options. Public policies can also play an important role in facilitating or hindering the adoption and spread of measures based on agricultural biodiversity.